2019
DOI: 10.1101/551465
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations between absolute neutrophil count and lymphocyte-predominant breast cancer

Abstract: 2Tumor-infiltrating lymphocytes (TILs) might be associated with host-cell mediated immunity, 3 which could be partly reflected by peripheral blood cell counts. We aimed to investigate 4 whether peripheral blood cell counts are associated with TILs in breast cancer. Between August 5 2016 and July 2018, we evaluated the percentage of stromal TILs in breast cancer patients who 6 underwent primary surgery, using the standardized methodology proposed by the international 7 TIL Working Group. Lymphocyte-predomina… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The TIL counts were measured as previously described [13,18,19]. TILs were scored according to the standardized methodology proposed by the international TIL Working Group [20].…”
Section: Tissue Microarray Sp142 Pd-l1 Assay and Other Studiesmentioning
confidence: 99%
“…The TIL counts were measured as previously described [13,18,19]. TILs were scored according to the standardized methodology proposed by the international TIL Working Group [20].…”
Section: Tissue Microarray Sp142 Pd-l1 Assay and Other Studiesmentioning
confidence: 99%
“…Tumor-infiltrating lymphocytes (TILs) are a specific histological feature of human cancers, reflecting an individual's immunological tumor response (27). Previous studies have reported that TILs may be associated with peripheral blood cells, such as the TLC and absolute neutrophil count (28,29). In esophageal cancer, the PNI and TIL score have been reported to be associated with clinical outcomes (30).…”
Section: A Operative Factorsmentioning
confidence: 99%
“…TILs have attracted recent attention with the development of immune checkpoint inhibitors. In addition, there were some reports TILs had the relationship between peripheral blood cells, such as TLC and absolute neutrophil count (ANC) [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…Lymphocyte-predominant breast cancer (LPBC), which has high TIL levels, has a good prognosis [22]. Lee et al reported a signi cant correlation between peripheral lymphocyte count and TILs in patients with cervical carcinoma [23], whereas Yoon et al reported a signi cant relationship between TILs and peripheral neutrophil count in breast cancer [24].…”
mentioning
confidence: 99%